2018
DOI: 10.2478/foli-2018-0001
|View full text |Cite
|
Sign up to set email alerts
|

Ownership and Perpetual Usufruct in the Valuation of Undeveloped Real Property on the Example of Parallel Markets

Abstract: The paper presents an analysis of the trade in undeveloped real property in two cases: the ownership title and perpetual usufruct. The aim was to find the relation between the values of these rights in parallel markets, which allows to evaluate a better type of right to the property with a worse one. Such a solution is justified when the data is lacking in the local market. The solution is also frequently encountered in the practice of a property appraiser (Dobek, Suchoń, Wajszczuk, Wielicki, 2009). In the emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The relation between the values of the ownership title and perpetual usufruct in case of undeveloped grounds for single-family houses in case of Poland was investigated by Foryś and Gaca (2018). In their study, they used the transactions (131 observations) concluded between the years of 2013-2015 in two districts of Bydgoszcz.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The relation between the values of the ownership title and perpetual usufruct in case of undeveloped grounds for single-family houses in case of Poland was investigated by Foryś and Gaca (2018). In their study, they used the transactions (131 observations) concluded between the years of 2013-2015 in two districts of Bydgoszcz.…”
Section: Literature Reviewmentioning
confidence: 99%
“…, 2014, p. 54). Perpetual usufruct rights (Foryś and Gaca, 2018) may cause additional uncertainty in real estate development in Poland. An alternative to ownership transfer, perpetual usufruct is the right to use the land for a period between 40 and 99 years.…”
Section: Introductionmentioning
confidence: 99%